Hormonomic Changes Driving the Negative Impact of Broomrape on Plant Host Interactions with Arbuscular Mycorrhizal Fungi - Mishev, Kiril; Dobrev, Petre I; Lacek, Jozef; Filepová, Roberta; Yuperlieva-Mateeva, Bistra; Kostadinova, Anelia; Hristeva, Tsveta (International journal of molecular sciences, 2021)
Belowground interactions of plants with other organisms in the rhizosphere rely on extensive small-molecule communication. Chemical signals released from host plant roots ensure the development of beneficial arbuscular mycorrhizal (AM) fungi which in turn modulate host plant growth and stress tolerance. However, parasitic plants have adopted the capacity to sense the same signaling molecules and to trigger their own seed germination in the immediate vicinity of host roots. The contribution of AM fungi and parasitic plants to the regulation of phytohormone levels in host plant roots and root exudates remains largely obscure. Here, we studied the hormonome in the model system comprising tobacco as a host plant, Phelipanche spp. as a holoparasitic plant, and the AM fungus Rhizophagus irregularis. Co-cultivation of tobacco with broomrape and AM fungi alone or in combination led to characteristic changes in the levels of endogenous and exuded abscisic acid, indole-3-acetic acid, cytokinins, salicylic acid, and orobanchol-type strigolactones. The hormonal content in exudates of broomrape-infested mycorrhizal roots resembled that in exudates of infested non-mycorrhizal roots and differed from that observed in exudates of non-infested mycorrhizal roots. Moreover, we observed a significant reduction in AM colonization of infested tobacco plants, pointing to a dominant role of the holoparasite within the tripartite system.
Keywords: heterocyklické sloučeniny tricyklické; houby; Nicotiana; Indoleacetic Acids; Chromatography, Liquid; root exudates; rhizosphere; cytokininy; Cytokinins; hmotnostní spektrometrie; mykorhiza; parasitic plants; laktony; Heterocyclic Compounds, 3-Ring; Fungi; Mycorrhizae; mycorrhizal fungi; strigolactones; Orobanche; Plant Roots; kyselina abscisová; kyseliny indoloctové; kyselina salicylová; plant hormones; Mass Spectrometry; interakce hostitele a patogenu; Salicylic Acid; Abscisic Acid; small-molecule communication; Host-Pathogen Interactions; kořeny rostlin; tabák; Lactones; chromatografie kapalinová